2018
DOI: 10.1557/jmr.2018.151
|View full text |Cite
|
Sign up to set email alerts
|

Texture size control by mixing glass microparticles with alkaline solution for crystalline silicon solar cells

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Since the texture not only is crucial to enhance light trapping but also has a high impact on the surface defect density, electrical properties of the c‐Si wafers, such as the lifetime of the minority charge carriers, are influenced as well. It was shown previously that a reduced pyramid size still results in excellent passivation and minority carrier lifetimes 4,5 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since the texture not only is crucial to enhance light trapping but also has a high impact on the surface defect density, electrical properties of the c‐Si wafers, such as the lifetime of the minority charge carriers, are influenced as well. It was shown previously that a reduced pyramid size still results in excellent passivation and minority carrier lifetimes 4,5 …”
Section: Introductionmentioning
confidence: 94%
“…It was shown previously that a reduced pyramid size still results in excellent passivation and minority carrier lifetimes. 4,5 To allow the wet processing of the perovskite absorber, which normally has a thickness of 0.5-1 μm, the pyramid height must be well below 1 μm to prevent the generation of local defects or shunts in the top cell. 1,4 Different methods can be used for the deposition of the perovskite film, such as blade-or slot-die coating, physical vapor deposition, or spin coating.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a perovskite layer with a thickness greater than the pyramid height need not be conformal and it can be deposited from solution. There is precedence for this approach: Ju et al and Nguyen et al have reported a silicon texturing process with pyramids smaller than 2 mm, 39,40 and several scalable solution-processing approaches that have been reported for single-junction perovskite solar cells 41 -including blade coating, 42,43 slot die coating, 44,45 and spray coating, 46,47 -may conceivably be adapted to this tandem application.…”
Section: Context and Scalementioning
confidence: 99%
“…The chemical solution process used for sub‐micrometer texturing is well compatible with the Si manufacturing process, and the cost of textured surface cleaning is low. [ 168 ] Moreover, surface texturing of the perovskite layer is expected to further improve light trapping efficiency, [ 136 ] although the corresponding technology has not yet been fully developed. Thus, the combination of sub‐micrometer texturing with the use of solution‐processed perovskite films should allow one to meet the demand for high‐efficiency and cost‐effective hybrid tandems.…”
Section: Interconnection Structure and Materialsmentioning
confidence: 99%